Frequency of Thymoma in Thymectomy Specimens in Myasthenic Patients (Medical Forum Monthly, 2024)
Objective: This study was carried out to determine the frequency of thymoma in different age groups and sexes in thymectomy specimens in Myasthenia Gravis patients.Study Design: Observational studyPlace and Duration of Study; The study was carried out in General Surgery Department at PIMS over a period of three years from 2009-2012. PIMS is a tertiary care centre where large population of Islamabad and Surrounding territory, including AJK, Gilgit Baltistan, Hazara division, Peshwar and nearby districts of Punjab gets treatment .Materials and Methods: A total of 30 patients selected at random, were included in this study. Patients were of different age groups, above 12 and under 52 years of either sex. Patients with poor medical control of disease with no contra indication for surgery. Patients with operable mediastinal mass (thymoma) were included. Generalized myasthenia gravis was diagnosed in patients. Pre-operative plasmaphoresis was carried out in all patients. Transsternal approach was used in all cases although now video assisted thoracoscopic thymectomy is becoming popular. Intraoperative findings were noted with emphasis on gross appearance and an informationby histopathological report (frozen section).Results: In our study 17 % thymectomy specimens turned out to be Thymoma. Male to female ratio was 3:2. Age range was 12 years to 52 years.Conclusion: All patients undergoing thymectomy for Myasthenia Gravis don’t have thymoma. Moreover all Thymomas are not associated with Myasthenia Gravis. Ages between 3rd to 5th decade are affected by thymoma and gender difference is very little.